The Educational Importance of Ethnic Music in the Initial Professional Training of Teachers - Jautakytė, Rasa (Acta Paedagogica Vilnensia, 1997)
The article analyses the importance of ethnic culture in the development of the teacher's personality. The author presents the ideas of prominent Lithuanian educators – S. Šalkauskis, A Maceina, Vydūnas, etc. – on ethnic music. The role of the teacher of music in national education is pointed out. The article describes a survey which was completed in Klaipėda University and was aimed at clarifying the students' outlook towards ethnic music.